Efficient two-party certificateless authenticated key agreement protocol under GDH assumption. (2019) - Xie, Yong; Wu, Libing; Shen, Jian; Li, Li
Security and efficiency are two key requirements for most of the authentication protocol, especially for the mobile wireless network. However, security and efficiency are a contradiction for the design of authentication protocol, it is hard to meet the two requirements simultaneously. Since certificateless public key cryptography (CL-PKC) has an advantage in wiping off key escrow problem, many certificateless authentication key agreement (CL_AKA) protocols have been proposed. The existing CL_AKA protocols may meet either security requirement well or efficiency requirement well, but cannot meet the two well. In this paper, we propose an efficient two-party CL_AKA protocol with strong security. We perform an in-depth security analysis in extended Canetti-Krawczyk (eCK) model to show the proposed CL_AKA protocol is provably secure. The performance analysis shows that the proposed protocol can meet the strong security and efficiency requirements simultaneously.